The Implications of UN Security Council Resolutions in Shaping the Dynamics of the Palestinian-Israel Peace Process: The Israel-Hamas War as a Case Study - Ahmed, Awara Hussein; Ali, Hemn Shawkat (Indonesian Journal of International Law, 2025)
The Israeli war on Gaza on 7 October 2023 has raised questions regarding the effectiveness of international institutions in promoting peace and security. The Security Council (SC) plays an important role in global conflict resolution. The Council's response to the bloody war in Gaza has been the subject of scrutiny, causing many to question its competence and impact on global stability. Therefore, this study aims to examine the participation and influence of the United Nations Security Council (UNSC) in shaping the dynamics of the Israel-Palestinian conflict, with a particular focus on the recent military conflict between Israelis and Palestinians in the Gaza Strip. A mixed-method design was used to provide a nuanced understanding of UNSC engagement, and it combines the qualitative analysis of diplomatic discourse with quantitative analysis of historical and new UNSC resolutions. Furthermore, the legal analysis method was used. The results showed a correlation between the escalation or de-escalation of the conflict in the Israel-Palestinian context and the intricate patterns of decision-making in the UNSC. These results emphasized the limitations and potential strengths of the UNSC, as well as providing insight into the viability or effectiveness in conflict resolution.